The comparison of topographic long profiles of gullies on Earth to gullies on Mars: A signal of water on Mars - Conway, S.; Balme, M.; Kreslavsky, M.; Murray, J.; Towner, Martin (Academic Press Inc., 2015)
The topographic signature of a landform can give important clues as to its formation process. Here, we have used topographic long profiles to study the process of gully formation on Mars. We studied topographic long profiles of gullies on Earth to (1) confirm that previously published generalisations of how long profile shape varies with process also applies at the kilometre-scale of martian gullies, and (2) use as a direct comparison with the martian data. We have compared 24 fluvial and 22 debris flow long profiles of terrestrial gullies derived from laser altimeter and GPS measurements, to 78 long profiles of a range of gullies on Mars derived from a stereo-photogrammetry point-matching technique. We have confirmed that this manual point-matching technique is reliable for the martian data by comparison with full digital elevation models. We used nine different characteristics of the long profiles, including slope and curvature parameters, to perform a canonical discriminant analysis, which allowed us to identify the variables most important for differentiating between fluvial and debris flow gullies on Earth.In agreement with published literature for larger-scale features, we found that terrestrial debris flow gullies tend to be steeper and less concave than fluvial gullies. We have found that gully long profiles on Mars can resemble long profiles of terrestrial gullies formed by either fluvial or debris flow processes, with slightly more affinity to fluvial systems. Gullies on Mars can only be weakly separated from those on Earth: they can be separated from terrestrial fluvial gullies on curvature parameters and from terrestrial debris flow gullies by slope parameters. In addition, we have found that different alcove types identified from planview morphology are also distinctive in terms of their long profile morphology: gullies which incise back into the bedrock are more similar to terrestrial debris flows whereas polar-pit gullies are most similar to terrestrial fluvial gullies. Our findings suggest that the presence of a bedrock alcove promotes debris flow behaviour in gullies on Mars.